2021
DOI: 10.3390/ijms22041876
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stop Codons within Prokaryotic Protein-Coding Genes Suggests Frequent Readthrough Events

Abstract: Nonsense mutations turn a coding (sense) codon into an in-frame stop codon that is assumed to result in a truncated protein product. Thus, nonsense substitutions are the hallmark of pseudogenes and are used to identify them. Here we show that in-frame stop codons within bacterial protein-coding genes are widespread. Their evolutionary conservation suggests that many of them are not pseudogenes, since they maintain dN/dS values (ratios of substitution rates at non-synonymous and synonymous sites) significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The comparison of pseudogenes with their functional homologs showed that most pseudogenes are truncated (480,349, 71%). Recent studies suggest that early stop codons in many truncated pseudogenes correspond to nonsense mutations (24), or transient alleles that may be reversed under purifying selection (25). Comparing the evolutionary rates of truncated and non-truncated pseudogenes we find that truncated pseudogenes are characterized by higher dN and dS, as well as higher dN/dS compared to non-truncated pseudogenes (Supplementary Figure S3), as is expected for DNA evolution following a relaxation of selection pressure (i.e., gene non-functionalization).…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of pseudogenes with their functional homologs showed that most pseudogenes are truncated (480,349, 71%). Recent studies suggest that early stop codons in many truncated pseudogenes correspond to nonsense mutations (24), or transient alleles that may be reversed under purifying selection (25). Comparing the evolutionary rates of truncated and non-truncated pseudogenes we find that truncated pseudogenes are characterized by higher dN and dS, as well as higher dN/dS compared to non-truncated pseudogenes (Supplementary Figure S3), as is expected for DNA evolution following a relaxation of selection pressure (i.e., gene non-functionalization).…”
Section: Resultsmentioning
confidence: 99%
“…The mean half-life of pseudogenes in Buchnera , an endocellular bacterial symbiont found in insects, is approximately 24 million years ( 61 ). Moreover, the dN/dS values (ratios of substitution rates at non-synonymous and synonymous sites) of pseudogenes are significantly lower than 1 ( 62 ), indicative of a strong purifying selection on pseudogenes, namely pseudogenes are still functional to some extent.…”
Section: Discussionmentioning
confidence: 97%
“…This is a conservative approach: after removal of this mutation, all probability values associated with ORF8b become even smaller. The reason why we did not remove the missense mutation is that although readthrough events are rare, they are still possible [ 40 ]. We also detected one tandem double substitution AGG -> GGT (Fig.…”
Section: Discussionmentioning
confidence: 99%